1989 piano, vocal, guitar - Swift, Taylor 1989- (Hal Leonard Corporation, 2014)
Presents arranged music for thirteen songs contained in an album of the same name
For voice and piano, with chord symbols and guitar chord diagrams
Keywords: Popular music / 2011-2020; Musique populaire / 2011-2020; Popular music; 2011-2020; Songs; Musique populaire